A simple heat-based alternative method for deparaffinization of histological sections significantly improves acid-fast staining results for Mycobacteria in tissue - Pedro F. Marinho; Thomas Hanscheid (MethodsX, 2023)
Histopathology is the study of how disease alters human and animal tissue and is based on the microscopic examination of stained tissue sections. To maintain tissue integrity, preserving it from degradation, it is initially fixed, primarily with formalin, before being treated with alcohol and organic solvents, allowing the infiltration of paraffin wax. The tissue can then be embedded in a mold and sectioned, usually at a thickness between 3 and 5 μm, before staining with dyes or antibodies to demonstrate specific components.As the paraffin wax is insoluble in water, it is necessary to remove it from the tissue section before applying any aqueous or water-based dye solution, to allow the tissue to successfully interact with the stain. This deparaffinization/hydration step is normally carried out using xylene, an organic solvent, followed by hydration using graded alcohols.However, this use of xylene has been shown to have detrimental effects on acid-fast stains (AFS), such as those employed to demonstrate Mycobacterium, including the causative agent of tuberculosis (TB), as the integrity of the lipid-rich wall present in these bacteria may be compromised using xylene.A simple, novel method, Projected Hot Air Deparaffinization (PHAD) removes the solid paraffin from the tissue section without the use of any solvents, which produces significantly improved staining results using AFS. PHAD relies on the projection of hot air onto the histological section to melt and remove paraffin from the tissue, which can be achieved using a common hairdryer. • PHAD relies on the projection of hot air onto the histological section which can be achieved using a common hairdryer. • The blowing force is such that melted paraffin is removed from the tissue in 20 min. • Subsequent hydration allows for using aqueous histological stains with success, such as the fluorescent auramine O acid-fast-stain.